The effect of special exercises accompanying nutritional supplements in the development of some respiratory indicators and achievement level for AdhamiyaYouth Club swimmers - FadhilAlwan, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Free swimming is one of the important types of water sports that take advantage of the water medium as a means to move through it through the movements of the arms, legs, trunk, and breathing, with the aim of improving human efficiency, not only from a physical point of view. functional and skill, but also from a psychological and social point of view, and even mentally. The study aimed to identify the values of the respiratory indicators under study and the level of achievement for the research sample, and the researcher hypothesized that there are statistically significant differences between the two pre-tests. And the dimensionality in the values of the respiratory indicators under study and the level of achievement, in favor of the post-test for the research sample. The researcher used the experimental method on 6 of the Adhamiya Youth Club swimmers, and after analyzing and treating the values of the studied functional indicators for the research sample, the researcher reached several conclusions, including that the special exercises used have a clear impact on the development of respiratory system work and the values of the indicators under study and through the results in the post-test. The recommendations were the necessity of following up the players by conducting periodic functional tests and knowing their functional status during the training year.